Network administrators survival guide - Deveriya, Anand (Cisco Press networking technology series., 2005)
The all-in-one practical guide to supporting your Cisco network Provides detailed tips for using freeware and open-source tools readily available from the Internet, including the reasons behind choosing a particular tool Refer to a single source for common Cisco network administration issues Dedicated section for network security aids administrators in effectively dealing with security issues Deploy fully functional RADIUS and TACACS+ for servers for controlling access to Cisco devices Deploy Linux- and Windows-based syslog servers to centrally collect syslog information generated by Cisco devices Deploy Linux- and Windows-based network monitoring systems to monitor interface traffic through Cisco devices including routers, switches, VPN concentrators, and Cisco PIX® firewalls Use the trending feature of network monitoring systems for long-term network analysis and capacity planning Automatically detect and report configuration changes on Cisco IOS® Software-based devices and Cisco PIX firewalls Deploy Cisco-based VPNs in mixed environments using Linux- and Windows-based VPN servers Network Administrators Survival Guide solves many common network administration problems by providing administrators with an all-in-one practical guide to supporting Cisco® networks using freeware tools. It is a single reference source that explains particular issues, their significance for administrators, and the installation and configuration process for the tools. The solutions are Cisco centric and provide detail not available in generic online information. Network Administrators Survival Guide emphasizes solutions for network managers and administrators of small to medium-sized businesses and enterprises. Each chapter is broadly based on a network administration function, starting with an overview of the topic, followed by the methodology involved to accomplish that function. This includes the tools available, why they are the right choice, and their installation, configuration, and usage methods. For any given function, Network Administrators Survival Guide covers both Windows- and Linux-based tools as appropriate. Most of the Windows-based tools offer the advantage of GUI for ease of use, whereas the Linux-based tools are command-line based and can be used in automated scripts. Both are significant for network administrators. Based on author Anand Deveriya's extensive field experience, this practical guide to maintaining Cisco networks will save you signifi ...